Strategi Akomodasi Komunikasi Guru TK pada Proses Pembelajaran di Kelas - Madarina Rizqi Naufalia; Sandy Tegariyani Putri Santoso (Institut Agama Islam Negeri Madura, 2023)
This study aims to determine the communication accommodation strategies used by kindergarten teachers during the learning process and the patterns used. This research is a quantitative research with a type of survey research. Data collection techniques using closed questionnaires are distributed online through google forms. The results showed that kindergarten teachers who were respondents to the study used communication accommodation strategies in the learning process, both convergence and divergence. The majority of teachers use convergence strategies rather than divergence strategies. That is, the majority of kindergarten teachers organize, adjust or modify their communication behavior according to the characteristics of the pupils.